Program completion in the input language of GRINGO*. Issue 5 (23rd August 2017) - HARRISON, AMELIA; LIFSCHITZ, VLADIMIR; RAJU, DHANANJAY
Abstract: We argue that turning a logic program into a set of completed definitions can be sometimes thought of as the "reverse engineering" process of generating a set of conditions that could serve as a specification for it. Accordingly, it may be useful to define completion for a large class of Answer Set Programming (ASP) programs and to automate the process of generating and simplifying completion formulas. Examining the output produced by this kind of software may help programmers to see more clearly what their program does, and to what degree its behavior conforms with their expectations. As a step toward this goal, we propose here a definition of program completion for a large class of programs in the input language of the ASP groundergringo, and study its properties.